Aplicabilidade do ensaio de compressão de anel para determinar o coeficiente de atrito no ensaio de torneamento do aço ABNT 1045 - Thaís Ramos Capai Jardim (2023)
Friction in machining is difficult to determine due to the small areas of tool/chip and tool/part interface, high temperatures, stresses and deformations. Thus, several tribological tests were developed to simulate the cutting conditions and determine the coefficient of friction, such as the pin-on-face test, cylinder-on-face test and pin-on-cylinder. This work compares the coefficient of friction between ABNT 1045 steel and WC-10Co coated with AlCrN obtained by two methods: turning test and ring compression test. The characterization of the ABNT 1045 steel was carried out through chemical, microstructural and mechanical analysis. The microstructural analysis of the ring after deformation in the ring compression test observed the influence of the test temperature on the displacement of the neutral radius. The surface analysis of the rings and matrices of the compression test was performed using optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS) and roughness Ra, where it was observed the increase in roughness after the test and the presence of adhesive wear. The turning test was performed with oblique cutting at cutting speeds of 150 and 220 m/min. Acquisition of machining force component signals using a piezoelectric dynamometer. The ring compression test was carried out at temperatures of 200 and 400°C. Friction coefficients were obtained using mathematical models. Statistical analysis of the coefficient of friction indicated equivalence of the coefficient of friction in the turning test at a cutting speed of 150 m/min with the ring compression test at 200°C. As well as in the turning test at cutting speed 220 m/min with the ring compression test at 400°C.